KORELASI NILAI KOEFISIEN ARAH SERAT BETON TERHADAP KEKUATAN TARIK LENTUR PADA BETON DENGAN SERUTAN BAJA MAUPUN HAREX SF - Zulaicha, Lilis; Marwanto, Marwanto (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2015)
Concrete has high compressive strength that is capable of supporting a large and heavy structures. But concrete has a low tension strength and brittle nature (Brittle). The weakness of this concrete properties can be improved by providing treatment such as provide fiber. There are several fibers that can be used to improve the properties of concrete and one of them is the steel fibers. Steel fibers possess the strength and modulus of elasticity which is relatively high. Moreover steel fibers do not change the shape of the influence of alkali in the cement. Imposition in a long period o f time does not affect the mechanical properties of steel fiber. Bond in the composition of the mixture can be increased because fastening mechanically. The study used the steel shavings and fiber materials Harex SF. The aim of this examination was intended to determine the coefficient of concrete fiber orientation at the same time the value of flexural tension strength of concrete produced in the concrete mix wearing Harex SF fiber or steel shavings. Steel fiber used in this study using the percentage of 1 until 4 percent of the weight of the concrete mix and perform quality control for the split tension strength of concrete at 28 days. From this research, the percentage of 3 percent as the optimum value based on the ease of doing the concrete (workability) used for research flexural tension strength of concrete and fiber orientation coefficient of concrete in the concrete with steel shavings and concrete with fibers Harex SF. From the testing that has been done shows: flexural tension strength fiber-reinforced concrete Harex SF 3 percent of 5,037 MPa and flexural tension strength of concrete with steel shavings of 11,035 MPa and the coefficient offiber direction concrete well with fiber Harex SF and shavings o f steel both are between 0 and 1 (0 less than or equal to eta of phi less than or equal to 1) with an average value close to 0, which means both fibers are working properly so that is proven to increase the tension strength offlexural concrete.